URGENSI BIMBINGAN PRA NIKAH DALAM MENGUPAYAKAN KEHARMONISAN RUMAH TANGGA - Arif Hariyanto; Ach. Azaim Ibrahimy (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
Marriage is a very important dimension of life in human life. So it is not surprising that religions in the world regulate marriage issues even according to traditions or customs among local communities, and state institutions also do not lag behind in regulating marriages that apply among the community. The purpose of marriage according to the Islamic religion is to fulfill religious instructions in order to establish a harmonious, prosperous and happy family, harmony in exercising the rights and obligations of family members. Prosperous means the creation of inner and outer peace due to the fulfillment of life's and inner and outer needs, so that happiness arises, namely affection between family members Premarital guidance for those who are getting married is highly recommended because it provides provisions for both parties so that family life can be adjusted to religious guidance, and marriage can be able to give birth to a harmonious family